Chengshi gonggong changsuo huanjing weisheng
'Hygiene in the environment of urban public places.' Part of series "Thoroughly defeat the germ warfare of American imperialism. Everybody joins the patriotic hygienic campaign to prevent epidemics" (later slogan cropped from right side of poster). Printno. 0442.